2015
DOI: 10.14740/jocmr2011w
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Nodosum and Mycoplasma pneumoniae Infections in Childhood: Further Observations in Two Patients and a Literature Review

Abstract: Erythema nodosum (EN) is the most frequent panniculitis in childhood and has been associated with various conditions, such as infectious and autoimmune disorders, medications, and malignancies. The author reports on two children affected with EN associated with Mycoplasma pneumoniae infection, which occurred in one patient without pulmonary detection. The available literature on EN and M. pneumoniae infection in childhood is also reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Our review disclosed 11 erythema nodosum cases associated with M. pneumoniae infection [4,54,58,78,79,80,81,82,83]. No more than 1 case of erythema nodosum associated with M. pneumoniae respiratory infection was noted in 9 case series [4,79,84,85,86,87,88,89,90] including a total of 654 erythema nodosum cases not addressing this possible association.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review disclosed 11 erythema nodosum cases associated with M. pneumoniae infection [4,54,58,78,79,80,81,82,83]. No more than 1 case of erythema nodosum associated with M. pneumoniae respiratory infection was noted in 9 case series [4,79,84,85,86,87,88,89,90] including a total of 654 erythema nodosum cases not addressing this possible association.…”
Section: Resultsmentioning
confidence: 99%
“…Using the described strategy, 94 reports were retained for the final analysis [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97]: 1 in German [23], 1 in Italian […”
Section: Data Assessmentmentioning
confidence: 99%
“…An empiric antibiotic therapy was started without the ability to determine the infectious agent in one patient, and Mycoplasma pneumoniae ( M. pneumoniae ) was the identified agent in the other. There are many publications in literature reporting the association between M. pneumoniae and EN [ 21 , 22 ]. Unfortunately, the link between EN and mycoplasma infection has not been fully understood yet.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a retrospective study found that of 39 patients with EN, two were infected with M. pneu moniae and one had a concomitant acute streptococcal infection 6) . Greco et al described two children with EN caused by M. pneumoniae, one of whom had no respiratory symptoms 7) . Studies of EN associated with M. pneumoniae 37) found that the condition commonly appeared on the shins or arm and buttocks of females around 10 years of age and typically occurred 15 days after prodromal symptoms, such as fever.…”
Section: Case Reportmentioning
confidence: 99%